Mohd Zulkifli Mohd Ghazali [fotograf] : Pengarah Kerja UTM (1990-1992), Dekan Fakulti Kejuruteraan Awam (1992-1997), Timbalan Naib Canselor (HEP) (1997- ) - Mohd. Zulkifli Mohd. Ghazali, Tan Sri Prof. Ir. Dr., 1951-; Universiti Teknologi Malaysia
PSZJBL